2018
DOI: 10.1007/s10854-018-9911-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of electronic properties of Fe-doped TiO2 nanoparticles by X-ray photoemission spectroscopy

Abstract: The importance of investigating the electronic structure of Fe doped TiO2 nanoparticles lies in understanding their various magnetic and optical applications. In this study Fe doped TiO2 nanoparticles were synthesized by sol gel method in a wide range of Fe/Ti molar ratios (1, 3, 5, 8, and 10 %) and post annealing at 400, 600 and 800 o C in air. The structure and size of nanoparticles were studied by X-ray diffraction and transmission electron microscopy, respectively. Systematic study of the existing states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…The photoelectron peak of O 1s is found at binding energy of 529.9 eV that corresponds to the lattice oxygen in TiO2. This result is similar with previous study conducted by Nasralla et al [30]. The measuring binding energies of Cu p1/2 and Cu p3/2 are 951 and 931.9 eV, respectively.…”
Section: Physical and Chemical Characterizations Of Cuo/tio2 Photocatalystsupporting
confidence: 93%
“…The photoelectron peak of O 1s is found at binding energy of 529.9 eV that corresponds to the lattice oxygen in TiO2. This result is similar with previous study conducted by Nasralla et al [30]. The measuring binding energies of Cu p1/2 and Cu p3/2 are 951 and 931.9 eV, respectively.…”
Section: Physical and Chemical Characterizations Of Cuo/tio2 Photocatalystsupporting
confidence: 93%
“…Nevertheless, in terms of the increase of the TiO 2 photocatalytic activity with iron doping, some studies reported the opposite behavior. Multiple factors can contribute to the inconsistencies reported in the literature, including disparities in synthesis methods, annealing temperatures, the organic compounds used for the photocatalytic tests, and the concentration of the iron dopant [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the considerations that can be taken to overcome this weakness is by incorporating metals ions into TiO2 structure [19]. Among the wide range [17] of available choices, Fe 3+ was of tremendous interest owing to its similar ionic radii to Ti 4+ that facilitates incorporation into the crystal lattice of TiO2 [20][21][22]. On the other hand, Ag is also a promising promotor for TiO2 as it is a noble metal that could reduce the recombination rate of the photogenerated electrons and holes through the formation of the Schottky Barrier on the Ag-TiO2 interface.…”
Section: Introductionmentioning
confidence: 99%